The Golden Era of the Malaysian Film Industry: Cross-Cultural Dialogue and Negotiations of Ethnicity in a Budding Nation - Angeline Wong Wei Wei; Shanthini Pillai; Ong Puay Liu (Kajian Malaysia, 2018)
The period of the 1950s to the late 1960s has often been touted as the Golden Era of the Malaysian film industry. This paper examines the extent to which films of the Golden Era, specifically P. Ramlee's Sesudah Suboh (1967) and Gerimis (1968), i.e. two significant films of the era which portray stories about inter-ethnic romantic relationships, visualise the possibilities of inter-ethnic engagement through the films' narrative and the implied issues of ethnic and cultural differences. The discussion highlights the fact that there are significant moments of inter-ethnic dialogue and engagements between the characters within the narratives of the two films which outweigh the evidences of inter-ethnic prejudices that are portrayed in the films. The main conclusion that is derived from the film analysis is that the two films are significant spaces through which the borders between identities and cultures can be negotiated in the form of meaningful dialogue and engagement.